Analysis of FSW and TIG Aluminium 5052 Welded Joint Strength Due to The Effect of Working Temperature - Hartono Yudo; Razin Hilmy Baihaqi; Untung Budiarto (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2022)
Aluminium 5052 on ships can be used in LNG tanks, heat exchangers, bulkheads, and superstructures. Its characteristics that can be used in various types of construction in ships cause aluminium 5052 to meet various temperature conditions. The purpose of this research is to find out the strength of the FSW and TIG aluminium 5052 welded joints due to the effect of working temperature. The methods used are impact test and bending test of aluminium 5052 specimens immersed in liquid nitrogen at -1600C and heated in oven at 1660C. The average impact value of raw materials, FSW specimens, and TIG specimens immersed in liquid nitrogen at -1600C are 1.22 J/mm2, 0.2195 J/mm2, and 0.0663 J/mm2, respectively. The average impact value of raw materials, FSW specimens, and TIG specimens heated in an oven at 1660C are 1.3403 J/mm2, 0.1395 J/mm2, and 0.0870 J/mm2, respectively. The average bending stress of raw materials, FSW specimens, and TIG specimens immersed in liquid nitrogen at -1600C are 394.70 MPa, 85.82 MPa, and 299.49 MPa, respectively. The average bending stress of raw materials, FSW specimens, and TIG specimens heated in an oven at 1660C are 400.45 MPa, 148.58 MPa, and 318.55 MPa, respectively. Weld discontinuity observations shows that all raw material specimens do not have open discontinuities exceeding 3 mm, all FSW specimens have open discontinuities exceeding 3 mm, and TIG specimens shows varied results. The conclusion of this study shows that aluminium 5052 is a material that is resistant to temperature changes and is able to maintain its strength at various temperature conditions because aluminium is an FCC (Face Centered Cubic) material.